2000
DOI: 10.1053/joca.1999.0287
|View full text |Cite
|
Sign up to set email alerts
|

Influence of aging on the synthesis and morphology of the aggrecans synthesized by differentiated human articular chondrocytes

Abstract: The declining aggrecan synthesis rates and the decreased capability of assembling large molecular size aggregates with increasing age in humans illustrates a progressive failure of the repair function of articular cartilage cells in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
64
1
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 95 publications
(78 citation statements)
references
References 33 publications
12
64
1
1
Order By: Relevance
“…6). Verbruggen et al [38] noted that human chondrocytes (2-69 years old) do not proliferate at all once embedded in 1.5% autoclaved agarose, whereas Hauselmann et al [ 151 observed that human chondrocytes proliferate in 1% agarose, and proliferate more for younger donors, similar to our results ( Fig. 2A).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…6). Verbruggen et al [38] noted that human chondrocytes (2-69 years old) do not proliferate at all once embedded in 1.5% autoclaved agarose, whereas Hauselmann et al [ 151 observed that human chondrocytes proliferate in 1% agarose, and proliferate more for younger donors, similar to our results ( Fig. 2A).…”
Section: Discussionsupporting
confidence: 90%
“…2A). Agarose concentration, site of donor tissue, method of digestion for cell isolation, frequency of medium change, ascorbic acid concentration, and the choice of serum supplement are all potential parameters that could lead to the discrepan- cies between the results of Verbruggen et al [38] versus Hauselmann et al [15] and the results of our study. Kamada et al [23] observed an age-dependence in proliferation of bovine chondrocytes embedded in alginate, but they noted that fetal chondrocytes proliferate less than aged ones, a result different from our study.…”
Section: Discussioncontrasting
confidence: 62%
See 2 more Smart Citations
“…Decreased Bcl-2 expression with age is likely to be a contributing factor. It has also been demonstrated that there is decreased production of cartilage matrix proteins with age, especially in response to growth factors (Buckwalter et al, 1994;Bolton et al, 1999;Verbruggen et al, 2000). Maintenance of Bcl-2 expression may be important for maintaining cartilage matrix protein expression in vivo.…”
Section: Discussionmentioning
confidence: 99%